Reorganização do ensino de matemática no ciclo de alfabetização: avaliação das influências do PNAIC - Maciel, Marciane (2017)
Making children literate is not an easy task at the right age, so the challenge becomes even greater. Although we know that literacy is fundamental to the exercise of citizenship, we believe in literacy beyond the decoding of graphemes and phonemes. In this sense, the Public Policy for Continuing Education of Literacy Teachers, establishing the National Pact for Literacy in the Right Age (PNAIC), through Administrative Rule no. 867, of July 4, 2012, in addition to giving continuity and effectiveness to actions aimed at literacy, entered the educational universe, proposing a literacy in the literacy perspective. Regarding this, the present dissertation seeks to investigate the National Pact for Literacy in the Right Age influence in the continuity of the teaching practice in the mathematics teaching the literacy teachers the urban municipal schools at Abelardo Luz, SC, who participated in the PNAIC. Following this objective, a research problematizes the existence or not a (re) organization of the teaching practice, in Mathematics, the teachers that are part of the study. With regard to the methodology and method of investigation are concerned, the one, a bibliographic and documentary nature, and this one, analytical-reconstructive and interpretative, made possible that the research did not lose focus during the investigative process. In order to account for the demands arising from the research itself and from the requirements of the methodology and method chosen, the study is organized as follows: the first chapter deals with public policies on education, going beyond literacy policies to the PNAIC implementation. The second chapter discusses mathematical literacy and its obstacles. The third chapter deals with the research method applied in the research and, to show the results, in the fourth chapter are the analysis categories applied in the research, as well as the perceived convergences between them. Finally, in the final considerations, starting from the investigative process that led the study, the research highlights how the PNAIC influenced the teaching practice of teachers in the schools investigated.